ANALISIS PENGARUH PEMBIAYAAN MUSYARAKAH TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Elli Yani; Mukhlis M.Nur (LPPM Universitas Malikussaleh – Indonesia, 2020)
This study aims to determine and analyze the influence of musyarakah financing on the profitability of islamic bankks in indonesia. This research uses secondary data in the form of financial statements on musyarakah financing for islamic bankks during 2008-2012, which are accessed on www.ojk.go.id . The data analysis method used is a simple linear regression with the help of eviews program. The partial result shows that the t-statistic value of musyarakah financial is 15,29370 with a probability of 0,0000 which means lower that the value of α = 0,05. It concludes that musyarakah Financiang has a significant effect on the profitability (ROA) of islamic bankks listed on the financial Services Authority (OJK) in 2008-2012.